Volume 4: 20th Design for Manufacturing and the Life Cycle Conference; 9th International Conference on Micro- And Nanosystems 2015
DOI: 10.1115/detc2015-46565
|View full text |Cite
|
Sign up to set email alerts
|

Design and Topology Optimization of Lattice Structures Using Deformable Implicit Surfaces for Additive Manufacturing

Abstract: Additive manufacturing (AM) enables creation of objects with complex internal lattice structures for functional, aesthetic, structural and fabrication considerations. Several approaches for lattice generation and optimization, and their implementations in commercial systems exist. However, these commercial systems are typically independent from a CAD system, and therefore introduces workflow complexities for product lifecycle management. In this paper, we present a unified computer-aided framework for design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The skeleton was then thickened to form the actual lattice shape. Similar frameworks also exist in the prior works, for example, Arisoy et al (2015) and Gorguluarslan et al (2017). Arisoy et al demonstrated the generation of lattices by repeating the userdesigned lattice template shape along an axis aligned grid within their own geometric representation.…”
Section: Geometric Modeling Of Periodic Cellular Structuresmentioning
confidence: 95%
See 2 more Smart Citations
“…The skeleton was then thickened to form the actual lattice shape. Similar frameworks also exist in the prior works, for example, Arisoy et al (2015) and Gorguluarslan et al (2017). Arisoy et al demonstrated the generation of lattices by repeating the userdesigned lattice template shape along an axis aligned grid within their own geometric representation.…”
Section: Geometric Modeling Of Periodic Cellular Structuresmentioning
confidence: 95%
“…The implicit surface, C, is represented by the zero level set of f . f can be represented as isosurface functions, signed distance functions or discrete signed distance fields (Maldovan and Thomas, 2009;Arisoy et al, 2015;Pasko et al, 2011;Rumpf et al, 2015;Yoo, 2011b;Wang, 2007;Jones et al, 2006;Osher et al, 2004).…”
Section: Implicit Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Iso-surface extraction creates a mesh template from the object's surface for the cellular structure, facilitating the handling of complex geometries. However, this method is computationally intensive and has difficulties with high-curvature or complex topology surfaces [36,33]. Lastly, generative design pipelines offer automated modeling, analysis, and inverse design solving of conformal cellular structures through integrated optimization and FEA frameworks [37].…”
Section: Introductionmentioning
confidence: 99%
“…They are typically used to build lightweight [8] and robust structures [7,8] in engineering applications. Taking advantage of polygonal hollow shapes in lattice structures gives an added level of design flexibility [7,9]. Hollow polygonal shapes, including hexagons, triangles, rectangles/squares, and circles, provide numerous benefits [7] in lattice structures.…”
Section: Introductionmentioning
confidence: 99%